USM 52nd CONVOCATION 17-21 NOVEMBER 2015 - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, October 2015 – Approximately 5,555 graduands would be receiving their degrees and diplomas at the 52 Universiti Sains Malaysia (USM) Convocation Ceremony, to be held on Tuesday, 17 November 2015 until Saturday, 21 November 2015, for a duration of 5 days, in 9 sessions at the Dewan Tuanku Syed Putra USM Penang.